Chapter A cent'anni dai 'Fatti di Renzino'. Dalla celebrazione alle attività di Public History of Education nelle scuole di Foiano della Chiana - Bellacci, Francesco (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper shows Public History projects carried on in some school in Foiano della Chiana (Arezzo) in the last years. These projects were focused on the so-called "Fatti di Renzino", i.e. the army revolts organised in 1921 by socialists, communists and anarchiest in answer to fascists and their continuous, brutal attempts in sovverting liberal institutions.